O Fenômeno do mundo em ser e tempo de Heidegger - Ferreira, André Prock (2019)
This work aims to present a world phenomenon analysis – concept by Heidegger in the existential analytics developed in Being and Time (1927). The world is comprehended by Heidegger as one of the fundamental constitutive of Dasein. Moreover, we intend to show that this investigation performs a decisive function in the argumentative strategy of Heidegger. We will see that the world phenomenon shields a methodologic primacy from the delimitation of the median daily life, once it shows itself as a first horizon to where the Dasein turns in its existence. This way, since the beginning of Heidegger’s investigation, the phenomenon appeared as a question. For this, we will analyze: the phenomenological, in general traces, since its origins in Kant’s thinking and its development from Husserl thinking; some “ways” by which the notion of world is investigated by Husserl; and the indicatives presented by Heidegger in the beginning of the analytics. The guiding principle emerges from those analysis, that is, the pragmatic aspect assumed by the analytics, considering that the most immediate manner through which the Dasein relates itself with (and in) the world is not from a cognitive behavior, but from the usage of utensils. Consequently, we will consider the analysis of the world phenomenon developed by Heidegger in the treaty, presenting the elements regarded for us as fundamental for its elaboration. This way it is inserted in the investigation the theme of spatiality and the language as fundamental elements for its comprehension. From the analysis of these elements, the world phenomenon will reveal a referential complex structured in a “significative totality” (Bedeutungsganze). What lies in the scope of this elaboration of world phenomenon can be understood as a horizon of habitation that shields a poetic dimension. Finally, we present a comparative analysis between the elaboration we intend to develop and two other interpretations. This way, therefore, considering the coverage and the complexity of the world thematic, in a special manner, in the thinking of Heidegger, we do not intend to exhaust it, but to search to develop a first approach.